Solve the following system by graphing. \( x+y-6=0 \) \( x-y=0 \) What is the solution of the system? \( (-3,3) \) \( (3,3) \) \( (3,-3) \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To solve the system by graphing, we first need to rearrange the equations into slope-intercept form (y = mx + b). For the first equation \( x + y - 6 = 0 \): Rearranging gives us \( y = -x + 6 \). For the second equation \( x - y = 0 \): Rearranging gives us \( y = x \). Now, let's plot both lines. The first line has a negative slope, crossing the y-axis at 6, while the second line is a straight line at a 45-degree angle through the origin. To find the intersection point, we see where these two lines cross. Setting them equal to each other: \(-x + 6 = x\) This simplifies to \(2x = 6\) or \(x = 3\), and substituting back we find \(y = 3\). So, the solution to the system of equations is \( (3, 3) \). For the context, graphing systems of equations is not only a fascinating mathematical skill but also powerful in various fields such as economics, engineering, and physics! When you visualize equations, you get a clear sense of their relationships. And if you ever find yourself graphing complex systems on paper, remember to not rush! A common mistake is misplacing points or miscalculating intersections. Always double-check your graph points and calculations before concluding!